An Experimental and Theoretical Study on the Unexpected Catalytic Activity of Triethanolamine for the Carboxylative Cyclization of Propargylic Amines with CO2. Issue 9 (11th April 2017) - Zhao, Yuling; Qiu, Jikuan; Li, Zhiyong; Wang, Huiyong; Fan, Maohong; Wang, Jianji
Abstract: Chemical conversion of CO2 under atmospheric pressure and metal‐free conditions remains a great challenge. In this work, a series of alkanolamines, low‐cost and biodegradable bases, were used to catalyze the carboxylative cyclization of propargylic amines with CO2 . Among these alkanolamines, triethanolamine (TEOA) was found to be a highly efficient organocatalyst for this important transformation at atmospheric pressure, and a series of desired products were synthesized in good to excellent yields. After the reactions, TEOA could be easily recovered and reused without obvious reduction in the efficiency. DFT studies revealed that TEOA may activate CO2 to form a ring‐shaped carbonate intermediate that plays an important role in the catalysis of the reaction. This finding provides an effective and environmentally friendly alternative route for the production of 2‐oxazolidinones. Abstract : Tales of the unexpected : A series of alkanolamines, low‐cost and biodegradable bases, were used to catalyze the carboxylative cyclization of propargylic amines with CO2 . Triethanolamine (TEOA) was found to be a highly efficient organocatalyst for this important transformation at atmospheric pressure and a series of desired 2‐oxazolidinone products were synthesized in good to excellent yields.